Easing pandemic-related restrictions, easing psychosocial stress factors in families with infants and toddlers? Cross-sectional results of the three wave CoronabaBY study from Germany - Anna Friedmann; Catherine Buechel; Clara Seifert; Stefan Eber; Volker Mall; Ina Nehring (BMC, 2023)
Abstract Background Families with young children are particularly vulnerable for the stressors induced by the COVID-19 pandemic. However, studies on their psychosocial situation during the course of the crisis are still sparse. Methods In a comparison of three survey waves (wave I and III = high COVID-19 incidences), we cross-sectionally investigated the proportion of families (Ntotal = 2940) with children aged 0-3 years experiencing pandemic burden, parenting stress, and parental and child mental health problems in relation to COVID-19 incidences and restrictions in Southern Germany via validated questionnaires. Potential influencing factors were also explored. Results The number of parents with a high pandemic burden decreased over the course of the pandemic with a peak of 65.3% in wave I (significant changes except wave II versus III). Participants with high parenting stress significantly increased from 38.2% in wave I to 51.2% in wave III. The number of parents with symptoms of depression and anxiety remained constantly high with a maximum of 28.4% being affected. Infants with crying/sleeping problems increased significantly from 26.4% in wave I to 35.5% in wave III. Toddlers' emotional and behavioral problems showed a peak of 23.9% in wave III (no significant changes). Increased family conflicts were the strongest predictor for parenting stress (ß = 0.355), maternal (ß = 0.305), infants' (ß = 0.149) and toddlers' (ß = 0.216) mental health problems during the pandemic. Conclusions Psychosocial stress factors in families with infants and toddlers remained highly pronounced and even partly increased irrespective of pandemic events. The findings suggest a staggered negative impact of pandemic-related factors on young children's mental health. Promoting infants' mental health as well as strengthening parental resources by reducing parenting stress should be a top healthcare priority in the aftermath of COVID-19. Trial registration The study was pre-registered in OSF ( https://osf.io/search/?q=tksh5&page=1 )